Integrated Web Server-Based Ticket Booking and Passenger Motorboat Positioning System with GPS GT08 - Ratuloli, Magfhirah Auladina; Suharto, Nugroho; Mustafa, Lis Diana (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
The main transportation used in the NTT region is sea transportation. Because sea transportation is the main transportation within the province, ships not only carry passengers but also transport vehicles and logistical needs. Until now, passenger motor ships have not been equipped with a ship navigation system, because these ships are still very traditional. There is no ship position information system and online ship ticket ordering, which makes it difficult for the public. Payment is usually made when crew members go around to give tickets. However, due to the large number of passengers due to the ship’s limitations, the situation became less conducive and less safe. In fact, it often creates conditions because many passengers do not pay for ship tickets, causing losses to the owners. Based on the problems explained above, the aim of this research is to design a "Web Server Based GPS GT08 Integrated Passenger Motor Ship Position Information and Ticket Booking System", making it easier for people to order tickets online and reducing incidents of paying for ship tickets. Apart from that, both passengers and ship admins can see the current position of the ship.